1994
DOI: 10.1083/jcb.126.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and the hyaluronan receptor RHAMM promote focal adhesion turnover and transient tyrosine kinase activity.

Abstract: Abstract. The molecular mechanisms whereby hyaluronan (HA) stimulates cell motility was investigated in a C-H-ras transformed 10T 1/2 fibroblast cell line (C3). A significant (p < 0.001) stimulation of C3 cell motility with HA (10 ng/ml) was accompanied by an increase in protein tyrosine phosphorylation as detected by anti-phosphotyrosine antibodies using immunoblot analysis and immunofluorescence staining of cells. Tyrosine phosphorylation of several proteins was found to be both rapid and transient with phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
144
1
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(161 citation statements)
references
References 100 publications
8
144
1
8
Order By: Relevance
“…As mentioned above, removal of the pericellular coat of human smooth muscle cells by competition with oligosaccharides resulted in a flatter, more adherent phenotype, again consistent with an anti-adhesive property of the coat. Evidence of increased focal adhesion turnover following addition of hyaluronan to migrating cells highlights the dynamic role of the pericellular matrix [87]. Rapid uptake of the hyaluronan and translocation to the nucleus, with signaling mediated through RHAMM, was associated with increased motility.…”
Section: Pericellular Matrix Regulation Of Cell Adhesionmentioning
confidence: 99%
“…As mentioned above, removal of the pericellular coat of human smooth muscle cells by competition with oligosaccharides resulted in a flatter, more adherent phenotype, again consistent with an anti-adhesive property of the coat. Evidence of increased focal adhesion turnover following addition of hyaluronan to migrating cells highlights the dynamic role of the pericellular matrix [87]. Rapid uptake of the hyaluronan and translocation to the nucleus, with signaling mediated through RHAMM, was associated with increased motility.…”
Section: Pericellular Matrix Regulation Of Cell Adhesionmentioning
confidence: 99%
“…This result suggests that both oligomers and polymer act by similar mechanisms, possibly inhibiting a cellular event essential for tumor cell proliferation. Evidence for signal transduction in response to interactions of hyaluronan with cell surface CD44 (Lesley et al, 1993;Bourguignon et al, 1993;Galluzo et al, 1995;Taher et al, 1996) or RHAMM (Entwistle et al, 1996;Hall et al, 1994Hall et al, , 1995 has been reported. However, in some cases, the effects of hyaluronan oligomers have been shown to differ markedly from those of hyaluronan polymer (West and Kumar, 1989;Noble et al, 1993).…”
Section: Hyaluronan Oligomers Inhibit Tumor Growth In Vivomentioning
confidence: 99%
“…Previous work demonstrated that motility of human thymocytes was mediated by RHAMM [2,34,39], an HA receptor involved in signal transduction and turnover of focal adhesions [57]. Ex vivo, thymocytes bind HA almost exclusively via RHAMM despite their abundant expression of CD44 [S. L. Gares, M. Crainie, and L. M. Pilarski, unpublished results].…”
Section: Discussionmentioning
confidence: 95%